Public houses and house prices in Great Britain: a panel analysis. Issue 1 (2nd January 2021) - Cabras, Ignazio; Sohns, Franziska; Canduela, Jesus; Toms, Steve
ABSTRACT: This paper examines the relationship between public houses or 'pubs' and house prices in Great Britain. Using a unique dataset, comprising statistical indicators for 373 local authorities registered between 2005 and 2015, the authors investigate this relationship from a panel data perspective. The analysis identifies a strong positive association between an increase in the number of pubs and house prices, showing different patterns with regard to pubs located in urban, suburban and rural areas. Results offer an original contribution to the literature related to the economic value of pubs as important third places in Great Britain, providing the basis for potential policy choices aimed at supporting community investment.